JURIDICAL ANALYSIS OF MALANG REGENCY RELIGIOUS COURT JUDGMENT CONCERNING CANCELLATION OF MARRIAGE ISBAT ACCORDING TO MARRIAGE LAW AND ISLAMIC LAW - Desi Rahmawati; Hazar Kusmayanti; Fatmi Utarie Nasution (Jurnal Poros Hukum Padjadjaran, 2023)
Marriage Isbat is a validation of marriage. Not all application of marriage isbat are accepted, one of which is Decision No. 0637/Pdt.G/2021/PA.Kab.Mlg where the Religious Court decided to cancel the marriage isbat that has been granted. The main issue in Decision No. 0637/Pdt.G/2021/PA.Kab.Mlg is that the application of marriage isbat is formally flawed due to the lack of parties in it. The writing method used is a normative juridical method with a qualitative juridical analysis method. The purpose of this study is to find out the consideration of the Court in deciding this case and the legal consequences of the cancellation of marriage isbat according to Indonesian Marriage Law and Islamic Law. Based on the result of the study, the Judge’s consideration in Decision No. 0637/Pdt.G/2021/PA.Kab.Mlg is in accordance with the relevant regulations. Meanwhile the legal consequences of the marriage isbat cancellation is that the registered marital status is reverted to the unregistered marriage. Based on the Marriage Law, unregistered marriages have very detrimental effects for both wife and children. While based on Islamic law the legal consequences are the same as the validity of marriage based on the Marriage Law.